OCT ANGIOGRAPHY IN DISEASES OF THE VITREORETINAL INTERFACE - Dusová, J; Studnička, J; Stepanov, A; Breznayová, J; Beran, D; Tarková, A; Jirásková, N (Ceska a slovenska oftalmologie, 2021)
AIMS: Present the use of Optical Coherence Tomography Angiography (OCTA) in vitreoretinal interface diseases and results of macular capillary network evaluation before and after idiopathic macular hole surgery (IMD). METHODOLOGY: Prospective evaluation of functional results, anatomical and OCTA findings before and after IMD surgery. The group consists of 8 eyes of eight patients. Preoperatively and 1, 3 and 6 months after surgery, the best corrected visual acuity (BCVA) was examined, fundus photography was performed, examination of the macula by spectral-domain optical coherence tomography (SD OCT), determination of the stage of IMD according to Gases and also OCTA examination. The area of the foveal avascular zone (FAZ) and vascular density (VD) were evaluated by using of the OCTA. The operation was performed in all cases by transconjunctival suture 25G vitrectomy by one surgeon, always peeling the inner limiting membrane. An expansive gas, 7x 20% SF6, 1x 15% C3F8, was used for vitreous tamponade. RESULTS: In all 8 cases, the primary closure of the IMD occurred after the operation. The mean BCVA improved statistically significantly from 0.74 to 0.48 logMAR (p = 0.0023). The average FAZ area decreased from 0.345 mm² to 0.25 mm² after surgery (p = 0.0458). The mean VD increased from 7.93 mm-1 to 8.38 mm-1 (p = 0.2959). CONCLUSIONS: Assessment of the macular capillary network in patients with diseases of the vitreoretinal interface offers new findings and important details that can lead to prognostic information and a better understanding of the pathogenesis of the disease. We demonstrated a statistically significant reduction in FAZ in the eyes after successful IMD surgery and an indirect relationship between the improvement of BCVA and the change in FAZ area in our cohort.
Keywords: Epiretinal Membrane; Tomography, Optical Coherence; epiretinal membrane; idiopathic macular hole; Retinal Perforations; optická koherentní tomografie; lidé; OCT angiography; vitrektomie; vitreoretinal interface; Vitrectomy; retrospektivní studie; epiretinální membrána; angiografie; zraková ostrost; Visual Acuity; Retrospective Studies; Angiography; Pars plana vitrectomy; perforace sítnice; vitrectomy; Humans